PERAN BRAND BOROBUDUR DALAM PARIWISATA DAN WORLD HERITAGE - Muh Ariffudin Islam (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
Borobudur is one of numerous cultural products in Indonesia. As a cultural object, its existence provides a uniqueattraction as it contains historical value, a source of knowledge, and technology. Viewed from the economic and tourismperspective, Borobudur is a cultural asset which is economically profitable. As a historical object, many studies are stillbeing carried out on its artefacts. This research aims to discover the role of the Borobudur as a â€œbrand,â€ from the perspectiveof tourism and world heritage. This goal will be achieved through a qualitative research method, by means of a descriptiveanalyticalapproach which focuses in particular on the perspective of imagery as an entity. The research process was based ona discovery and correlation of data in order to accumulate as much information as possible about the â€œbrandingâ€ of a touristobject. From a research point of view, the results obtained from this study show that Borobudur is able to act as a tourist objectand destination both for the local community and international tourists. In addition, through various means of promotion asa world cultural heritage, Borobudur has managed to become an icon for religious tourism in Indonesia. This is also related tothe various media which act as a â€œbrandâ€ to form, develop, and create the identity of a tourism entity.Keywords: Borobudur, Brand, Tourism, World Heritage